EVALUATION OF OUTCOMES OF FIRST-TIME CESAREAN SECTIONS IN PREGNANT WOMEN AT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of primary cesarean sections among obstetric patients at Vinmec Times City International General Hospital, Hanoi.Methods: A cross-sectional descriptive study was conducted on 516 obstetric patients who underwent their first cesarean section at Vinmec Times City International General Hospital between January and December 2023.Results: The study of 516 patients undergoing primary cesarean section recorded a mean age of 29.9 ± 4.8 years, with 80.1% of pregnant women are ≤ 35 years old. The rate of intrapartum cesarean sections (57.8%) was higher than that of elective procedures. The predominant anesthetic techniques were spinal and epidural anesthesia (97.4%), with a low anesthesia conversion rate (1.4%). The majority of patients (91.1%) only required prophylactic antibiotics, and 99.6% underwent a transverse suprapubic incision. The average intraoperative blood loss was 424.7 ± 293.6 ml. The mean postoperative hospital stay was 4 ± 0.4 days, with 89.7% of patients being discharged on the fourth day. The postoperative readmission rate was very low (0.8%), and the postpartum follow-up rate was recorded at 72.5%.Conclusion: Primary cesarean sections at the Vinmec Times City International General Hospital achieved safe outcomes and favorable recovery. The standardization of regional anesthesia protocols, the use of prophylactic antibiotics, and the application of transverse incision techniques effectively controlled blood loss, optimized hospital stays, and maintained low readmission rates.
Keywords: Primary cesarean section, surgical outcomes, obstetric patients.